CURRENT PRACTICE ON FOUNDATION DESIGN OF HIGH-RISE BUILDINGS IN BANGKOK, THAILAND - K. Amornfa; N. Phienwej; P. Kitpayuck (Lowland Technology International, 2012)
Assessment was made on the current practice on foundation design of high-rise buildings in Bangkok, Thailand to explore rooms for improvement. An interview survey revealed that the current design practice was dominated by structural engineers. They commonly used the conventional method of analysis, namely the combined stress equation, as well as the plate on springs analysis. The finding from the survey study indicates the current design practice does not encourage an optimal design outcome in term of cost effectiveness. The second part of the study is to explore the benefit in adopting the piled raft foundation design concept. A comparative study on the results of the 3dimensional finite element (3D FEM) analysis and various analysis methods currently used. The results show that the plate on pile springs method which neglects pile-pile and raft-pile interaction give results significantly different from that of the 3D FEM. The 3D FEM shows that only about 70-80% of total building loads are carried by piles when raft is placed in the stiff clay layer. The number of piles in the piled raft foundation can be significantly reduced particularly if the true piled raft foundation concept is adopted, while the foundation settlement only increases slightly.